Kebijakan Moneter Islam Dalam Upaya Mengendalikan Inflasi - Sari, Yovita (Jurnal Ilmiah Ekonomi Islam, 2024)
Abstract This research aims to analyze Islamic monetary policy in an effort to control inflation. This research uses the literature study method to analyze the latest literature and research regarding Islamic monetary policy. This method allows researchers to get a more comprehensive picture of Islamic monetary policy in an effort to control inflation. This literature and research can be obtained from various sources, such as scientific journals and websites. Based on research results, Islamic monetary policy has the potential to control inflation. Islamic monetary policies can be used to control the money supply, increase people's purchasing power, and encourage sustainable economic growth. It is hoped that this research can provide practitioners with a better understanding of Islamic monetary policy. This better understanding can help practitioners to implement Islamic monetary policy more effectively and efficiently. It is also hoped that this research can contribute to Islamic monetary policy theory. This analysis can be used to develop a more comprehensive theory of Islamic monetary policy.